Analyzing micro-level changes and minimalist techniques in Steve Reich’s "Piano Phase’" - Sailendra Bedantara Gunawan (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2022)
In the historical development of Western music in the 20th century, a related interesting phenomenon of the minimalist music genre developed in America. Minimalist music is a style of music based on limited materials and micro changes in those materials. Among the composers who fall into this musical genre category iscomposer Steve Reich, who wrote a work for two pianos entitled "Piano Phase." This writing aims to reveal the limitations of musical material and changes at a micro level that occur in the work "Piano Phase" throughmusical analysis. The method used is content analysis based on two documents: sheet music and examplesof audio recording. From the analysis results, there are short melodic sentences with micro changes throughrhythm shifts using the accelerando technique. The changes made occur in three parts that have a pleasanttexture difference. The work "Piano Phase" has a unique composition technique, namely through Accelerandotempo changes can cause changes in the melody texture indirectly expected.